Estrogen receptors mediate the antidepressant effects of aerobic exercise: A possible new mechanism - Zhou, Ruixue; Wang, Zhisheng; Zhou, Bojun; Yu, Zixin; Wu, Chongyun; Hou, Jun; Cheng, Ken; Liu, Timon Chengyi (Frontiers in Aging Neuroscience, 2022)
Purpose: This study aimed to examine whether aerobic exercise exerts mood-modulating effects through an oestrogen signalling mechanism. Method: Ovariectomised rats (age, 13 weeks) were divided into two groups. One group was tested when rats were 14 or 22 weeks old or in the sixth week after 3 weeks of chronic restraint stress. Rats in the other group were initially subjected to chronic restraint stress after ovariectomy and were subsequently subjected to placebo treatment or oestradiol (E2) replacement therapy, aerobic training or oestrogen receptor antagonist treatment. The cognitive (Barnes maze and 3-chamber social tests), anxiety-like (open-field and elevated plus maze tests) and depression-like (sucrose preference and forced swim tests) behaviours of rats in both groups were analysed to study the effects of oestrogen depletion or aerobic exercise. Results: Rats did not develop depressive symptoms immediately after ovariectomy; however, the symptoms became more pronounced with a gradual decrease in ovarian hormone levels. Compared with the placebo or control groups, the exercise and E2 groups showed improved performance in all behavioral test tasks, and the antidepressant effects of aerobic exercise were comparable to those of oestrogen. Moreover, the oestrogen receptor antagonist is markedly inhibited the antidepressant effects of aerobic exercise . Conclusion: Oestrogen receptors can mediate the antidepressant effects of aerobic exercise. In addition, an increasingly fragile ovarian hormonal environment underlies chronic restraint stress-induced depression.